New Communism Museum Invites Visitors To 'Travel Back' To Cold-War Bulgaria - Tizard, Will (2023)
Faded Communist Party signs, chipped kitchenware, and political speeches on a dusty record player are on display at Evgeni Mladenov's newly opened communism museum in the Bulgarian mountain village of Banite. The time capsule brings visitors back to the 1980s and immerses them in the Cold War past.
Keywords: 2023-08 August